2017
DOI: 10.1016/j.jhazmat.2017.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Promoted oxidation of diclofenac with ferrate (Fe(VI)): Role of ABTS as the electron shuttle

Abstract: Reaction of Fe(VI) with 2,2'-azino-bis-(3-ethylbenzothiazoline -6-sulfonate) (ABTS) is widely adopted to determine aqueous ferrate (Fe(VI)) concentration based on ABTS formation. Interestingly, this study found that the addition of ABTS could accelerate the oxidation of diclofenac (DCF) by Fe(VI) significantly. Observed first-order rate constant of DCF in the presence of 30μM ABTS was found to be 36.2 folds of that without ABTS, with values of 3.08 and 0.085min, respectively. It was partly attributed to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…At [ABTS] 0 /[Fe(VI)] 0 < 1.0, Fe(IV) is more likely to dominate the substrate degradation in the long run. In Dong' study, 28 the addition of a small amount of ABTS ([ABTS] 0 /[Fe(VI)] 0 < 0.2) could accelerate Fe(VI) oxidation of diclofenac in the course of 600 s at pH 8.0, which was explained by the possible involvement of more powerful oxidants, Fe(V) and ABTS •+ , generated from the reaction of Fe(VI) and ABTS. However, the kinetic simulation by the model in this study suggested a different explanation.…”
Section: Reactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…At [ABTS] 0 /[Fe(VI)] 0 < 1.0, Fe(IV) is more likely to dominate the substrate degradation in the long run. In Dong' study, 28 the addition of a small amount of ABTS ([ABTS] 0 /[Fe(VI)] 0 < 0.2) could accelerate Fe(VI) oxidation of diclofenac in the course of 600 s at pH 8.0, which was explained by the possible involvement of more powerful oxidants, Fe(V) and ABTS •+ , generated from the reaction of Fe(VI) and ABTS. However, the kinetic simulation by the model in this study suggested a different explanation.…”
Section: Reactionsmentioning
confidence: 97%
“…Meanwhile, Dong's study 28 reported that [ABTS] 0 /[Fe-(VI)] 0 > 10 was recommended for using the ABTS method for Fe(VI) determination in the presence of organic substrates (e.g., diclofenac) because an excess amount of ABTS could maintain the stability of ABTS •+ by inhibiting it from possible reaction with the substrate. This dilemma may render difficult application of the ABTS method for determination of Fe(VI) in the presence of substrates (e.g., amino acids, phenol, and alcohol) 46 susceptible to ABTS •+ oxidation, unless a new observed stoichiometry between Fe(VI) and ABTS •+ (i.e., >1) was applied when [ABTS] 0 /[Fe(VI)] 0 was greater than 10.…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant reaction mechanism and the type of the dominating oxidants of these reaction systems warrant in-depth investigation. Dong et al (2017) found that ABTS, acting as the electron shuttle, accelerated the reaction of DCF with Fe(VI) over a wide pH range. It was proposed that Fe(VI) can oxidize ABTS to ABTS + , which was responsible for the enhanced oxidation of DCF (Dong et al, 2017).…”
Section: Feomentioning
confidence: 99%
“…Dong et al (2017) found that ABTS, acting as the electron shuttle, accelerated the reaction of DCF with Fe(VI) over a wide pH range. It was proposed that Fe(VI) can oxidize ABTS to ABTS + , which was responsible for the enhanced oxidation of DCF (Dong et al, 2017). However, the potential promoting effects of the in situ generated Fe(V)/ Fe(IV) were not considered.…”
Section: Feomentioning
confidence: 99%